Snow cover setting-up dates in the north of Eurasia: relations and feedback to the macro-scale atmospheric circulation - V. V. Popova; A. V. Shiryaeva; P. A. Morozova (Лëд и снег, 2015)
Variations of snow cover onset data in 1950–2008 based on daily snow depth data collected at first-order meteorological stations of the former USSR compiled at the Russia Institute of Hydrometeorological Information are analyzed in order to reveal climatic norms, relations with macro-scale atmospheric circulation and influence of snow cover anomalies on strengthening/weakening of westerly basing on observational data and results of simulation using model Planet Simulator, as well. Patterns of mean snow cover setting-up data and their correlation with temperature of the Northern Hemisphere extra-tropical land presented in Fig. 1 show that the most sensible changes observed in last decade are caused by temperature trend since 1990th. For the most portion of the studied territory variations of snow cover setting-up data may be explained by the circulation indices in the terms of Northern Hemisphere Teleconnection Patterns: Scand, EA–WR, WP and NAO (Fig. 2). Role of the Scand and EA–WR (see Fig. 2, а, в, г) is recognized as the most significant.Changes of snow cover extent calculated on the base of snow cover onset data over the Russia territory, and its western and eastern parts as well, for the second decade of October (Fig. 3) demonstrate significant difference in variability between eastern and western regions. Eastern part of territory essentially differs by lower both year-to-year and long-term variations in the contrast to the western part, characterized by high variance including long-term tendencies: increase in 1950–70th and decrease in 1970–80 and during last six years. Nevertheless relations between snow cover anomalies and Arctic Oscillation (AO) index appear to be significant exceptionally for the eastern part of the territory. In the same time negative linear correlation revealed between snow extent and AO index changes during 1950–2008 from statistically insignificant values (in 1950–70 and 1996–2008) to coefficient values –0.82 ÷ –0.85 in 1973–1994 (Fig. 4, а, б). Results of numerical experiments on simulation of observed October snow cover anomaly in 1976 and its impact on Northern Hemisphere sea level pressure in winter months approved potential ability of abrupt increase of albedo caused by snow cover onset to influence on weakening of westerly and negative temperature anomalies in North Eurasia (Fig. 5). Evidently, based on observational data and results of modeling one should conclude that autumn snow cover anomalies in North are able to effect on macro-scale circulation regime in winter, but in condition of weakening of other major factors influencing on circulation, for example sea surface temperature over the oceans. In any case, correlation analysis of earth observations shows that snow cover extent anomalies could not be recognized as cause of negative AO anomalies and severe winters in North Eurasia in last decade.